Evidence-based medicine : how to practice and teach it - Straus, Sharon E.; Glasziou, Paul ;Richardson, W. Scott ;Haynes, R. Brian (Edinburg, New York : Elsevier Churchill Livingstone, 2011)
Evidence Based Medicine provides a clear explanation of the central questions: how to ask answerable clinical questions; how to translate them into effective searches for the best evidence; how to critically appraise that evidence for its validity and importance; and how to integrate it with patients' values and preferences. Constitutes a traditional way of presenting ideas about EBM. It explains how to ask answerable clinical questions, translate them into effective searches for the best evidence, critically appraise that evidence for its validity and importance, integrate it with patients' values and preferences, assess the practice of EBM. Additional materials, including resources for practicing EBM can be downloaded to PDAs, contain clinical examples, critical appraisals and background papers from other healthcare disciplines such as nursing and occupational therapy with links to various evidence resources. A supporting website for this book also provides updates and new materials
Asking answerable clinical questions Acquiring the evidence: how to find current best evidence and have current best evidence find us Appraising the evidence Therapy Diagnosis and screening Prognosis Harm Evaluation Teaching EBM
Includes index.
Keywords: EVIDENCE-BASED MEDICINE